2017
DOI: 10.3390/vaccines5010003
|View full text |Cite
|
Sign up to set email alerts
|

A Protective Vaccine against Chlamydia Genital Infection Using Vault Nanoparticles without an Added Adjuvant

Abstract: Chlamydia trachomatis genital infection is the most common sexually transmitted bacterial disease, causing a significant burden to females due to reproductive dysfunction. Intensive screening and antibiotic treatment are unable to completely prevent female reproductive dysfunction, thus, efforts have become focused on developing a vaccine. A major impediment is identifying a safe and effective adjuvant which induces cluster of differentiation 4 (CD4) cells with attributes capable of halting genital infection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Previous studies showed that a Chlamydia -specific IFNγ monofunctional Th1 clone was not protective, whereas a clone producing IFNγ and TNF cleared C. muridarum infection in nude mice (15). Vaccine models have shown that antigens and adjuvants generating polyfunctional (IFNγ+ TNF+) Th1 cells were more protective than IFNγ monofunctional Th1 cells (16, 17), and this protection has been observed in immunogenicity studies investigating single (18, 19) or multiple chlamydial antigens (2023). …”
Section: Introductionmentioning
confidence: 98%
“…Previous studies showed that a Chlamydia -specific IFNγ monofunctional Th1 clone was not protective, whereas a clone producing IFNγ and TNF cleared C. muridarum infection in nude mice (15). Vaccine models have shown that antigens and adjuvants generating polyfunctional (IFNγ+ TNF+) Th1 cells were more protective than IFNγ monofunctional Th1 cells (16, 17), and this protection has been observed in immunogenicity studies investigating single (18, 19) or multiple chlamydial antigens (2023). …”
Section: Introductionmentioning
confidence: 98%
“…Vaults are eukaryotic ribonucleoproteins assembly of a cage-like barrel-shaped structure (approximately 70 nm × 40 nm × 40 nm) made from the major vault protein (MVP) [63] . It has been shown that increased antigen-specific CD4 + T cell response with a reduction in genital bacterial load and inflammation was observed after Chlamydia muridarum polymorphic membrane protein G-1(PmpG) encapsulating vaults were administered intranasally [64] .…”
Section: Protein/peptide-based Nanovaccinesmentioning
confidence: 99%
“…Interestingly, the MOMP‐loaded vault nanoparticles did not stimulate TLR signaling pathways but triggered the production of IL‐1β via the activation of inflammasomes. Following intranasal immunization with vault nanocapsules loaded with either chlamydial MOMP or PmpG proteins, significant antigen‐specific antibodies and mucosal cellular responses were developed and reduced bacterial burden was observed in mice challenged with genital chlamydial infection …”
Section: Nanoformulations For Antibacterial Vaccinationmentioning
confidence: 99%
“…The self‐assembled vault protein has been exploited as a vaccine carrier to encapsulate chlamydial MOMP or antigens derived from polymorphic membrane protein G‐1 (PmpG) . The vault nanocapsules are under 100 nm in size and can be readily uptaken by dendritic cells.…”
Section: Challenges and Opportunities In Antibacterial Vaccinationmentioning
confidence: 99%